THE EFFECTIVENESS OF INTERVENTION PROGRAMS: CHANGING PERSPECTIVES OF PARENTS AGAINST THE FINAL RESULTS OF LEARNING IN KINDERGARTEN - Nila Fitria; Nurfadilah Nurfadilah (UPI Kampus Cibiru, 2018)
Abstract:. The purpose of this study is to test the effectiveness of parenting seminars to change the perspective of the parents towards the end results of learning in kindergarten. This research was conducted with quantitative methods with this type of survey research. Questionnaire in this tudy was made in the form of open ended questions. Overall it was concluded that at the time of pre test 37% still expect read write count (calistung) programs conducted in kindergartens. While 63% of respondents change of perspective, they no longer prioritize read write count (calistung) or cognitive aspects as the final results of the study children in kindergarten. parental perspective changes include the establishment of character, social skills, and creative.Keyword: Intervention Programs, Parents Perspectives, Kindergarten Abstrak: Tujuan penelitian ini adalah untuk menguji keefektifan parenting seminar untuk mengubah perspektif orang tua terhadap hasil akhir pembelajaran di taman kanak-kanak. Penelitian ini dilakukan dengan metode kuantitatif dengan jenis penelitian survei. Kuesioner dalam putusan ini dibuat dalam bentuk pertanyaan terbuka. Secara keseluruhan disimpulkan bahwa pada saat tes awal 37% masih mengharapkan program baca tulis (calistung) dilakukan di taman kanak-kanak. Sementara 63% responden mengubah perspektif, mereka tidak lagi memprioritaskan membaca menulis hitungan (calistung) atau aspek kognitif sebagai hasil akhir dari studi anak-anak di taman kanak-kanak. perubahan perspektif orang tua termasuk pembentukan karakter, keterampilan sosial, dan kreatif.Kata Kunci: Program Intervensi, Perspektif Orangtua, Taman kanak-kanak